Cos x = -12/13
sin x = -sqrt(13^2 - 12^2) / 13 = -5/13
tan x = 5/12
tan x/2 = (1 - cos x) / sin x = 1 - (-12/13) / -5/13 = 25/13 * -13/5 = -5
2sin^2 x/2 = 1 - cos x = 1 - (-12/13) = 25/13
sin^2 x/2 = 25/13 / 2 = 25/26
sin x/2 = 5/√26
sin x/2 / cos x/2 = tan x/2
cos x/2 = sin x/2 / tan x/2 = 5/√26 / -5 = -1/√26
sin x/2 = 5/√26
cos x/2 = -1/√26
tan x/2 = -5
Answer:
I'm pretty sure its 11
first orginize the numbers in numerical order
second the medj an is the middle numbe, if they are to find the mean of those two only
Answer:
4th one: A kite is the answer.
Answer:
A
Step-by-step explanation:
The area (A) of a triangle is calculated as
A = bh ( b is the base and h the perpendicular height )
Here b = 13 and h = 4 , thus
A = × 13 × 4 = × 52 = 26 units² → A
The sign of the product of that equation would be negative.